2015
DOI: 10.1002/bip.22634
|View full text |Cite
|
Sign up to set email alerts
|

Azide‐rich peptides via an on‐resin diazotransfer reaction

Abstract: Azide-containing amino acids are valuable building blocks in peptide chemistry, because azides are robust partners in several bioorthogonal reactions. Replacing polar amino acids with apolar, azide-containing amino acids in solid-phase peptide synthesis can be tricky, especially when multiple azide residues are to be introduced in the amino acid sequence. We present a strategy for effectively incorporating multiple azide-containing residues site-specifically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…11 Because of the simplicity of the design and compact size of the peptides, a family of α-helical “LK” peptides has been developed as self-assembling modules for biomaterials. 12 Starting from an amino acid sequence similar to these α-helical “LK” peptides, 13 we replaced two surface lysine residues with residues bearing water-soluble poly(alkyl ether) dendrons in the side chain.…”
mentioning
confidence: 99%
“…11 Because of the simplicity of the design and compact size of the peptides, a family of α-helical “LK” peptides has been developed as self-assembling modules for biomaterials. 12 Starting from an amino acid sequence similar to these α-helical “LK” peptides, 13 we replaced two surface lysine residues with residues bearing water-soluble poly(alkyl ether) dendrons in the side chain.…”
mentioning
confidence: 99%
“…The same polar and non-polar residues were used in our previously reported α-helical bundle-forming peptide-dendron hybrids. 32, 33, 54, 55 The side-chain amino group of each lysine residue is efficiently acylated using dendritic pentafluorophenyl esters. 54 DeGrado and Lear have shown that a seven-residue peptide with alternating leucine and lysine residues self-assembles into a β-sheet structure in buffered aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Rudimentary protein design rules offer a foundation from which to construct functional materials via programmable hierarchical organization of peptide-dendron hybrids. The recent report of self-organizable α-helix bundle-forming peptide-dendron hybrids 32, 33, 54, 55 is a promising starting point because natural helix bundles exhibit diverse functionality. 67, 68 Indeed, functional hybrid materials based on α-helix bundle-forming peptide-polymer conjugates have validated the concept of designing binding sites for light-harvesting chromophores in polymeric films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Peptides as highly attractive molecular structures have played key roles in biological research and therapeutic applications and they possess a wide range of physiological and cellular functions. [6][7][8] Advances in this regard are due to discovery of solid-supported synthesis 9,10 and the development of reagents and methods for direct amide formation. 7 Nevertheless, novel methods for the rapid production of these biopolymers are constantly being explored.…”
Section: Introductionmentioning
confidence: 99%